IDENTIFIKASI SENYAWA STEROID DARI PANGSA KULIT DURIAN (Durio zibethinus) - Yusiranna; Ilmiati Illing (Cokroaminoto Journal of Chemical Science, 2019)
Plants are natural ingredients that are widely used as traditional medicines and have been used for a long time by the people of Indonesia, even more popular both for the purpose of health care, treatment, and beauty, one of which is the use of durian rind as an anti-cholesterol drug based on their knowledge for generations. Although it is not yet equipped with scientifically convincing data regarding the content of active compounds that make it a nutritious drug, scientific research is needed in the form of identifying the steroid compounds contained therein. This research used maceration extraction method. A total of 50 grams of durian skin share powder was soaked with 96% ethanol which was carried out for 3 days with replacement fluid. Furthermore, the identification of secondary metabolite compounds by the Gas Chromatography-Mass Spectroscopy (GC-MS) Agilent 7890A-5975C method. Based on the results of a study conducted a share of positive durian skin containing a group of steroid compounds in the form of beta-sitosterol.